Basal Ganglia Location of Subependymal Giant Cell Astrocytomas in Two Infants - (:unkn) unknown (ELSEVIER SCIENCE INC, 2010)
Subependymal giant cell astrocytomas are benign tumors that constitute one of the primary features of tuberous sclerosis. Two infants with tuberous sclerosis had very unusual subependymal giant cell astrocytomas, confirmed on biopsy in one of the infants. In both cases, contrast-enhanced cranial magnetic resonance imaging suggested a calcified intra-axial mass with diffuse basal ganglia involvement extending into the lateral ventricle. Computed tomography confirmed calcification in both cases. The first patient had right temporal lobectomy for intractable epilepsy. Biopsy of the basal ganglia lesion in that case suggested subependymal giant cell astrocytoma. In infants, subependymal giant cell astrocytomas can present with unusual morphology and may feature diffuse basal ganglia involvement and severe calcification. (C) 2010 by Elsevier Inc. All rights reserved.
Keywords: PARTIAL SEIZURES; TUBEROUS SCLEROSIS; SPASMS